Seedling Response of Iranian Barley Landraces to Pyrenophora teres f. teres and Pyrenophora teres f. maculata - Arzu Çelik Oğuz; Amir Rahimi; Aziz Karakaya (Journal of Agricultural Sciences)
Net blotch caused by Pyrenophora teres is an important pathogen of barley plants worldwide. There are two biotypes of the fungus. Pyrenophora teres f. teres (Ptt) causes the net form of the disease and Pyrenophora teres f. maculata (Ptm) causes the spot form of the disease. Barley landraces are good sources of disease resistance. In this study, seedling response of 25 barley landraces obtained from different regions of northwest Iran to 3 single spore isolates of Ptt and 3 single spore isolates of Ptm were determined under greenhouse conditions. Differences in virulence among the isolates were evident. Some landraces showed different responses to different isolates. Landraces # 9 and # 16 showed moderately resistant reactions to one isolate of Ptt and showed moderately resistant-moderately susceptible reactions to 2 isolates of Ptt. Landraces # 7, # 11, # 15, # 17, # 21, # 22, # 23 and # 25 showed moderately resistant-moderately susceptible reactions to all 3 isolates of Ptt. Landrace # 23 showed resistant-moderately resistant reaction to one isolate of Ptm and showed moderately resistant reactions to 2 isolates of Ptm. Landrace # 16 showed moderately resistant reactions to all isolates of Ptm. Landraces # 11, # 15, # 21 and # 25 showed moderately resistant reaction to one isolate of Ptm and showed moderately resistant-moderately susceptible reactions to 2 isolates of Ptm. Landraces that exhibited reactions between resistant and moderately resistant-moderately susceptible range could be used as a direct seeding material to the field or could be used as breeding materials.